PROGNOSIS AND NEW THERAPEUTIC APPROACHES IN CHRONIC LYMPHOCYTIC LEUKEMIA TREATMENT - Otašević, Vladimir D; Mihaljević, Biljana; Antić, Darko (Medicinski podmladak, 2019)
Chronic lymphocytic leukemia (CLL) is the most common leukemia in the Western world, comprising about 30% of all leukemias in Europe and United States. Also, it represents one of the most active hematological disease regarding clinical trials. Nearly 80% of CLL patients have some chromosomal aberration, with following being emphasized due to its frequency and importance: 13q14 deletion (del13q14), 11q22-q23 deletion (del11q), chromosome 12 trisomy, 17p deletion (del17p) or/and tumor suppressor gene TP53 mutation. The use of new therapeutic agents in CLL treatment has markedly improved survival and quality of life of CLL patients. Ibrutinib, Bruton’s kinase inhibitor (BTK), is approved for first line therapy for CLL patients with del17p or TP53 mutation, as well for relapsed/refractory CLL patients (R/R CLL). The use of venetoclax, antiapoptotic protein bcl-2 inhibitor, is indicated for R/R CLL patients who are resistant to ibrutinib or for whose ibrutinib is contraindicated (use of anticoagulant therapy; increased bleeding risk). Phosphoinositide 3-kinase (PI3K), idelalisib (in combination with rituximab) and duvelisib (monotherapy), are approved for treatment of R/R CLL patients. The PI3K inhibitors are rarely used in treatment of R/R CLL patients before ibrutinib or venetoclax, primarily because of unfavourable safety profile of these drugs. New therapeutic agents are providing CLL patients longer overall survival and progression free survival, especially for CLL patients with adverse prognostic factors.